The Effectiveness of Project-Based Learning through Vlog to Improve Pre-Schoolers’ Vocabulary Mastery - Widia Yunita; M. Zaim; Hermawati Syarif; Yetti Zainil (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to find the impact of project-based learning using vlogs in improving the vocabulary skills of Early Childhood Education (PAUD) students. Participants in this study were 60 students. Sampling was done randomly. The method used is a one-group experiment. This study provides treatment for group experiments using pre-test and post-test. The research instrument has been tested using content validity by three supervisors with doctoral degrees. The results of the study concluded that the approach or learning method with learning media based on the student's background and the situation of the online learning environment had a significant effect on improving student learning outcomes. The concept of project-based learning applied through vlog design in PAUD classes has had a major impact on increasing students' vocabulary. The results of the study also have implications for teachers' understanding in solving problems through joint or individual projects that direct students to use their learning experiences and seek information to produce good vlogs.